PENCAK SILAT DALAM TARI WIRENG DI SURAKARTA - Mathias Supriyanto (Institut Seni Indonesia Surakarta, 2009)
The Art tradition life residing in kraton environment, is in general influened by king power, because result of tradition in this dance tradition diffused many by top kick king his day. One example Bedhaya Anglir dance, this dance have heroic theme to depicting Raden Said (Mangkunegara I) fight against Pangeran Mangkubumi I. Besides Overcast Bedhaya Anglir still many other soldier dances, that is type dance Wireng. Type dance its Wireng composition using many taken away from pencak silat. In composition dance Wireng there is two form move pencak silat, first pencak silat motion which have distilisasi; both pencak silat motion which still purification (wadag), like Bogis danceKeyword : Wireng, Heroic, pencak silat.